TRANSLATION SHIFT FROM ENGLISH INTO INDONESIA ON THE BAD GUYS SUBTITLING - Sulaiman, Salma R; Sama, Gratiana; Doi, Maksimilianus; Ngatu, Simon P K (Lantern: Journal of Language and Literature, 2024)
This study aims at explore the types of translation shifts in the subtitles of the movie The Bad Guys. This research is based on Catford's theory of shifts and utilizes a qualitative descriptive method. The data collected involves translations found in the dialogues of the characters Wolf, Snake, and Diane Foxington, focusing on words, phrases, clauses, and sentences that contain shifts. The results show that all types of shifts are found in the translated text of the movie "The Bad Guys." From the 247 shifts identified, there are 9 level shifts and 238 category shifts, in which, in detail, 98 data are classified as state shifts, 9 data are classified as class shifts, 123 data are classified as unit shifts, and 8 data are classified as intra-system shifts.